THE CHARACTERISTICS OF FORMING THE VOLUNTARY ASPECTS OF STUDENTS IN PROFESSIONAL DIRECTION - Eminjon Aliyevich Ergashev (Galaxy International Interdisciplinary Research Journal, 2022)
The article explains the importance of the volitional process from their individual characteristics and the importance of the formation of risk characteristics when directing students to the profession.